Ruins - Dillon, Brian; Dillon, Brian, 1969-; Arriola, Magali; Ballard, J.G.; Baudrillard, Jean; Whitechapel Art Gallery (London : Whitechapel Gallery, 2011)
Arceneaux, Edgar ; Balka, Miroslaw ; Becher, Bernd ; Becher, Hilla ; Beshty, Walead ; Boyce, Martin ; Byrne, Gerard ; Chodzko, Adam ; Deller, Jeremy ; Eydel, Katja ; Ferreira, Ângela ; Gaillard, Cyprien ; Gonzalez-Foerster, Dominique ; Hiller, Susan ; Hiorns, Roger ; Islam, Runa ; Kabakov, Ilya ; Koester, Joachim ; Kusmirowski, Robert ; Leonard, Zoe ; Lutter, Vera; Macuga, Goshka ; Margolles, Teresa ; Margreiter, Dorit ; Martins, Edgar ; Mehretu, Julie ; Müller, Christian-Philipp ; Nelson, Mike ; Olowska, Paulina ; The Otolith Group ; Parreno, Phillipe ; Perret, Mai-Thu ; Raad, Walid; The Atlas Group ; Shawcross, Conrad ; Smithson, Robert ; Whiteread, Rachel ; Wilson, Jane ; Wilson, Louise
"Co-published by Whitechapel Gallery and The MIT Press"--T.p. verso.
Formerly CIP.
boek
Keywords: Ruins in art; Ruins in literature; Arts, Modern -- 20th century; Arts, Modern -- 21st century; Aesthetics